Collusive Benchmark Rates Fixing - Nuria Boot; Timo Klein; Maarten-Pieter Schinkel (Tinbergen Institute, 2017)
The fixing of the Libor and Euribor benchmark rates has proven vulnerable to manipulation. Individual rate-setters may have incentives to fraudulently distort their submissions. For the contributing banks to collectively agree on the direction in which to rig the rate, however, their interests need to be sufficiently aligned. In this paper we develop cartel theory to show how an interbank lending rates cartel can be sustained by preemptive portfolio changes. Exchange of information facilitates front running that allows members to reduce conflicts in their trading books. Designated banks then engage in eligible transactions rigging to justify their submissions. As the cartel is not able to always find stable cooperative submissions against occasional extreme exposure values, there is episodic recourse to non-cooperative quoting. Periods of heightened volatility in the rates may be indicative of cartelization. Recent reforms to broaden the class of transactions eligible for submission may reduce the level of manipulation, but can lead to more frequent collusive quoting.
Keywords: E43; G14; G21; K21; L41; 330; Libor; Euribor; IRD; banking; cartel; insider trading